Current Trends in International Environmental Protection - Etinski, Rodoljub; Stanivuković, Maja; Đajić, Sanja; Đundić, Petar; Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
This article represents the overview of certain new trends in international environmental protection. The results of the research are organized in several sections: international legal sources (international agreements, international legal principles, soft law), human rights (Aarhus Convention, human rights in relation to climate change, right to water), procedural mechanisms available for the protection of environment (ICJ, CJEU, international procedures available to individuals, international investment arbitration, national courts). The article focuses not only on new developments which illustrate innovative approaches to environmental protection but also detects a number of problems in relation to their effective implementation and enforcement.